2019
DOI: 10.4187/respcare.06422
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the Ventilator Automated Displayed Respiratory Mechanics in Passive and Active Breathing Conditions: A Bench Study

Abstract: BACKGROUND: New-generation ventilators display dynamic measures of respiratory mechanics, such as compliance, resistance, and auto-PEEP. Knowledge of the respiratory mechanics is paramount to clinicians at the bedside. These calculations are obtained automatically by using the least squares fitting method of the equation of motion. The accuracy of these calculations in static and dynamic conditions have not been fully validated or examined in different clinical conditions or various ventilator modes. METHODS: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Another way of breath-to-breath automatic calculation of the dynamic respiratory mechanics (compliance, resistance, and auto-PEEP) without the need for any pause maneuvers is termed the least square fitting method, which uses regression analysis of the airway pressure, flow, and volume curves and applies it to the equation of motion (below). Those measurements are available in many new-generation ventilators [ 24 ]; however, those calculations might not be accurate in the actively breathing patient compared with the passive patient with no effort given the unknown value of the Pmus ( Table 1 , Equation 3).…”
Section: Clinical Usementioning
confidence: 99%
“…Another way of breath-to-breath automatic calculation of the dynamic respiratory mechanics (compliance, resistance, and auto-PEEP) without the need for any pause maneuvers is termed the least square fitting method, which uses regression analysis of the airway pressure, flow, and volume curves and applies it to the equation of motion (below). Those measurements are available in many new-generation ventilators [ 24 ]; however, those calculations might not be accurate in the actively breathing patient compared with the passive patient with no effort given the unknown value of the Pmus ( Table 1 , Equation 3).…”
Section: Clinical Usementioning
confidence: 99%
“…Daoud et al ( 12 ) evaluated the accuracy of the lung mechanics measurements displayed by the mechanical ventilator using the least squares method, which uses the equation of motion together with pressure, volume and flow data, to estimate lung compliance and resistance. The authors observed that these values are not reliable, especially during active breathing, as they overestimate compliance and underestimate resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The authors observed that these values are not reliable, especially during active breathing, as they overestimate compliance and underestimate resistance. The use of occlusion at the end of inspiration when performing these measurements was selected because this technique is easy and fast to perform in clinical practice; ( 12 ) thus, this technique was used in all measurements performed in the present study to ensure the nonoccurrence of measurement bias.…”
Section: Discussionmentioning
confidence: 99%
“…To mimic representative ICU patients [ 9 ], the performance of the device was tested using the ASL 5000 lung model (Ingmar Medical, Pittsburgh, PA, USA). Standard ventilator circuits (Intersurgical ® , ntersurgical Ltd., Berkshire, UK) and heat-and-moisture exchangers (HEPA Light Isogard ® , Gibeck, Gibeck® Iso-Gard HEPA light, Teleflex Inc., Morrisville, NC, USA) were used.…”
Section: Evaluation Protocolmentioning
confidence: 99%